Improving the Organization and Management System of Labor Protection in Industrial Enterprises - Samanov Ruslan Kholbotaevich (Researchparks Publishing, 2022)
This article examines the issues of effective organization of the work process in industrial enterprises, personnel policy, enterprise development and joint management, strategic and operational aspects of human resources management in the enterprise, and examination of knowledge on labor protection.